New insights into how cancer cells regulate glucose uptake by protein phosphorylation - Henriques, Andreia (2018)
Cancer cells require increased glucose supply to sustain proliferation. One mechanism involves increased expression of glucose transporter (GLUT) genes. But insulin has revealed that protein phosphorylation is another key mechanism in glucose uptake regulation: insulin binding to responsive cells triggers a signalling cascade with phosphorylation of TBC1D4, a negative regulator of endosomal GLUT trafficking, so that more transporters are inserted into the plasma membrane.